PENGARUH PENGETAHUAN WAJIB PAJAK, SOSIALISASI PAJAK, DAN PENERAPAN APLIKASI SAMSAT DIGITAL NASIONAL (SIGNAL) TERHADAP KEPATUHAN WAJIB PAJAK DI KABUPATEN TANGERANG - Valencia Lauwrenza; Wulandari Agustiningsih (JURNAL PAJAK INDONESIA, 2023)
This study aims to show whether or not there is an influence between taxpayer knowledge, tax socialization and the application of the national digital samsat application (SIGNAL) in the Tangerang district. The independent variables of taxpayer knowledge, tax socialization, and application of the national digital samsat application (SIGNAL) with the dependent variable are taxpayer compliance. Primary data will be collected by distributing questionnaires online (google form). Questionnaire assessment using a Likert scale. The number of samples is 100 respondents who are in the Tangerang Regency area and have used the SIGNAL application in terms of processing tax documents and paying motor vehicle taxes. The results of the study show that taxpayer knowledge and application of the national digital samsat application (SIGNAL) affect taxpayer compliance in Tangerang district. Tax socialization has no positive effect on taxpayer compliance in Tangerang district. Based on this research, the national digital samsat application (SIGNAL) is further improved and socialized to the public because in addition to the high knowledge of taxpayers, the application of the SIGNAL application can also increase taxpayer compliance in paying and administering tax documents related to motorized vehicle taxes, especially in the Tangerang district area.